The Gulag handbook : an encyclopedia dictionary of Soviet penitentiary institutions and terms related to the forced labor camps - Jacques Rossi ; translated from the Russian by William A. Burhans. (Paragon House, 1989)
Entries are in Russian, in Russian alphabetical order; explanatory text in English.Translation of: Spravochnik po Gulagu."A PWPA book."Includes indexes and bibliography, p. 579-586.